Study on the Released of Land for Chinese Capitalists to Growth Banana in Sing District, Luang Namtha Province - Lochamyeu, Chanthavong; Briatia, Xoxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This study was to elucidate the released of land area for Chinese capitalists renting to growth banana in Sing District, Luang Namtha Province. Aim of the study was: (1) to find the reasons those farmers released their areas for Chinese capitalists to growth banana and (2) to find that what will be happened to farmers after banana plantation in Sing District, Luang Namtha Province. Total number of interviewer were 68 families, whose have a land released for Chinese capitalists renting for banana plantation. The interviewer from Ban Namdath Mai 38 families and Namdath Someboun 30 families was selected. Period of the study was 3 months (28th February to 28th April, 2017). Results found that the reason of farmers released their land areas for Chinese capitalists renting because of surrounding area more than 26.5% have already rented for Chinese capitalist to plant banana, about 2.90% were from farmer self they want to release their areas for Chinese capitalists and 82.4% of farmers said that renting rate (renting cost) was higher than product price sale in the market, more than 1.5% of farmers believe that renting land for Chinese capitalists can have more money than sale product in the market, and 94.1% also believe that renting land for Chinese capitalists is the way to easy for earn big money, 1.5% said that they got many experiences and techniques from Chinese capitalist. However, the main problem after banana plantation of Chinese capitalists in Sing District, Luang Namtha Province was toxicity of chemical flood into the river covered 44.1%, waste of chemical contaminated plastic bags covered 19.1%, farmer have no cultivation areas covered 5.9%, other waste impacted to environment covered 2.9%, cannot update the soil covered 4.4%, Chinese capitalists left out and do not pay renting covered 38.2%, air and water pollution covered with 4.4%, problem beetween farmers and Chinese capitalists covered with 35.3% and Chinese capitalists did not follow by the agreement document covered about 7.4%, Impact to environment and farmers cultivation covered 44.1%, impact to aquatic animals 2.9%, impact to the diversity of edible plants 5.9%, impact to famers 11.8% and other external 8.8%, respectively.